Tool heads prime saccades - Pilacinski, Artur (Sci Rep, 2021)
Tools are wielded by their handles, but a lot of information about their function comes from their heads (the action-ends). Here we investigated whether eye saccadic movements are primed by tool handles, or whether they are primed by tool heads. We measured human saccadic reaction times while subjects were performing an attentional task. We found that saccades were executed quicker when performed to the side congruent with the tool head, even though “toolness” was irrelevant for the task. Our results show that heads are automatically processed by the visual system to orient eye movements, indicating that eyes are attracted by functional parts of manipulable objects and by the characteristic information these parts convey.